Telomeres as hotspots for innate immunity and inflammation - Nassour, Joe; Przetocka, Sara; Karlseder, Jan (DNA repair, 2024)
Aging is marked by the gradual accumulation of deleterious changes that disrupt organ function, creating an altered physiological state that is permissive for the onset of prevalent human diseases. While the exact mechanisms governing aging remain a subject of ongoing research, there are several cellular and molecular hallmarks that contribute to this biological process. This review focuses on two factors, namely telomere dysfunction and inflammation, which have emerged as crucial contributors to the aging process. We aim to discuss the mechanistic connections between these two distinct hallmarks and provide compelling evidence highlighting the loss of telomere protection as a driver of pro-inflammatory states associated with aging. By reevaluating the interplay between telomeres, innate immunity, and inflammation, we present novel perspectives on the etiology of aging and its associated diseases.